Study on Trajectory Motion of Intra Row Weeder - K. Raju Yadav; A. Suredrakumar; P. Dhananchezhiyan; Kavitha; S. D. Sivakumar; M. R. Duraisamy (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
Weeding is a critical and labor-intensive process. A mechanical hydraulic actuated weeder was developed by adopting a rotary mechanism that consisted of a rotating blade with the diameter and width of the weeding blade. Instead of lab and field evaluation, the weeding tool’s path was traced using the SolidWorks software to reduce cost and time and improve performance and accuracy. A 3D model of the intra-row weeder complex with relative handling modules was analyzed for motion using the SolidWorks Motion system. The blade center moved parallel to the crop row, with the swept area passing between the plant’s forming a acycloidal path in rows. Controlled laboratory experiments were conducted to analyze the effects of the weeding blade geometry, forward speed (1, 1.2 and 1.4 km/h), and weeding tool speed (30, 40, 50 and 60 rpm). The results showed that plant damage was much less at a speed of 1.2 km/h and a weeding tool speed of 50 rpm was found to be optimum for effective weeding operation with plant-to-plant spacing of 45 cm in the experimental test rig.